Usability of a Mobile Application on Anemia Prevention among Adolescents - Rahayu, Sri; Said, Mohamed Saifulaman Mohamed; Sansuwito, Tukimin; Rachmaniah, Dini (Fakultas Ilmu-ilmu Kesehatan, 2024)
The availability and usability of a smartphone application in Indonesia for preventing anemia, particularly for adolescents, are understudied due to the large number of health applications available for hematologic diseases. This research aims to provide a comprehensive overview of a mobile application development process to prevent anemia among adolescents and test its usability to the end user. The study analyzed the usability of a hybrid application called